2023
DOI: 10.1111/nph.19073
|View full text |Cite|
|
Sign up to set email alerts
|

Ptr1 and ZAR1 immune receptors confer overlapping and distinct bacterial pathogen effector specificities

Ye Jin Ahn,
Haseong Kim,
Sera Choi
et al.

Abstract: Summary Some nucleotide‐binding and leucine‐rich repeat receptors (NLRs) indirectly detect pathogen effectors by monitoring their host targets. In Arabidopsis thaliana, RIN4 is targeted by multiple sequence‐unrelated effectors and activates immune responses mediated by RPM1 and RPS2. These effectors trigger cell death in Nicotiana benthamiana, but the corresponding NLRs have yet not been identified. To identify N. benthamiana NLRs (NbNLRs) that recognize Arabidopsis RIN4‐targeting effectors, we conducted a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…The CC‐NLR‐encoding Ptr1 gene, which was identified recently in a wild relative of tomato, S. lycopersicoides , confers resistance to Pst , Xanthomonas spp., and Ralstonia pseudosolanacearum by detecting multiple sequence‐diverse type III effectors, including AvrRpt2 (Ahn, Kim, et al., 2023; Kim et al., 2022, 2023; Mazo‐Molina et al., 2019, 2020; Tsakiri et al., 2023). It is unknown whether any Nrc protein is required for Ptr1‐mediated immunity.…”
Section: Resultsmentioning
confidence: 99%
“…The CC‐NLR‐encoding Ptr1 gene, which was identified recently in a wild relative of tomato, S. lycopersicoides , confers resistance to Pst , Xanthomonas spp., and Ralstonia pseudosolanacearum by detecting multiple sequence‐diverse type III effectors, including AvrRpt2 (Ahn, Kim, et al., 2023; Kim et al., 2022, 2023; Mazo‐Molina et al., 2019, 2020; Tsakiri et al., 2023). It is unknown whether any Nrc protein is required for Ptr1‐mediated immunity.…”
Section: Resultsmentioning
confidence: 99%
“…While HopZ5-triggered HR was reduced by m1 expression in the transient assay, ion leakage was only partially reduced (Figure 1e). Ahn et al 27 found that Nb ZAR1 was also involved in the recognition of HopZ5 in N. benthamiana. Therefore, we identified two silencing fragments from our hairpin library, m16 and u38, which correspond to the nucleotide-binding-ARC (NB-ARC) domain or the coiled-coil (CC) domain of Nb ZAR1 , respectively (Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…Several RIN4-related NLR genes have been identified, including At RPS2 , Md Mr5 , Sl Ptr1 , Gm RPG1r , Gm RPG1b , At RPM1 , At ZAR1 , and Nb ZAR1 15,1719,26,27 . To understand the broader relationships of Ac PTR1 homologues with these NLR proteins involved in recognition of RIN4-associated effectors, the NB-ARC domains of each NLR protein were also included in our phylogenetic analysis (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations